Reversal of Azithromycin Resistance in Staphylococcus saprophyticus by Baicalin - Wang, Jinli; Meng, Jinwu; Zhu, Jinyue; Qiu, Tianxin; Wang, Wenjia; Ding, Jinxue; Liu, Zhenguang; Li, Kun; Wang, Deyun; Liu, Jiaguo; Wu, Yi (Frontiers in Veterinary Science, 2022)
In recent years, the efficacy of antibiotics has been threatened by the evolution of bacterial resistance. We previously demonstrated that baicalin (Bac) showed synergies with azithromycin (Azm) against Azm-resistant Staphylococcus saprophyticus (ARSS). The aim of this study was to explore the roles of Bac in reversing the resistance of ARSS to Azm. The ARSS was sequentially passaged for 20 days with the sub-MIC (minimum inhibitory concentration) of Bac. The strain that recovered sensitivity to Azm was named Azm-sensitive S. saprophyticus (ASSS). The sub-MIC of Bac reversed the resistance of ARSS to Azm. The MIC of Azm against the ASSS strain was 0.488 mg/l, and it was stable within 20 passages. The highest rate of resistance reversal reached 3.09% after ARSS was exposed to 31.25 mg/l Bac for 20 days. Furthermore, semiquantitative biofilm and RT-PCR assays reflected that the ability of biofilm formation and the transcript levels of msrA, mphC, and virulence-associated genes in the ASSS strain were significantly lower than those of the ARSS strain (p < 0.05). Simultaneously, Azm delayed the start time of death, alleviated the injury of the kidney, and decreased the bacterial burden in organs and cytokine levels in mice infected with ASSS. In contrast, Azm did not have a good therapeutic effect on mice infected with ARSS. Therefore, Bac has the potential to be an agent that reversed the resistance of ARSS to Azm.